An Analysis on the Interaction effect between Advertising Frame and Audience Frame: A Quantitative Study with Young Women of Pondicherry (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Advertisements are constantly criticized for stereotyping women. Several studies are done exploring its effects on body image of audience; however, this study is unique in exploring the aspect of ‘Influence of advertising frame on constructing the audience frame’ in regards to body image. Providing an insight on how images of women are constructed – framed in advertising and how it works in the minds of young women, this study is an effort to examine the potential influence of advertisements on audience frame in the context of body image perception. A quantitative approach was adopted exploring the artifice behind body image perception of young women in Pondicherry. A total of 106 respondents including both students and working women of age group between 17 and 27 are taken as samples. The study revealed that there exist a linear correlation between the ‘Ideal women’ framed by the advertisements through various media and construction of audience frame in conjunction to their body image. How to cite this article: Subashini K. An Analysis on the Interaction effect between Advertising Frame and Audience Frame: A Quantitative Study with Young Women of Pondicherry. J Adv Res Jour Mass Comm 2018; 5(4): 54-58.